2013
DOI: 10.2298/avb1306473t
|View full text |Cite
|
Sign up to set email alerts
|

The serum protein electrophoretic pattern and acute phase proteins concentrations in calves with chronic respiratory diseases

Abstract: The aim of this study was to evaluate the serum proteins electrophoretic pattern and the concentrations of acute phase proteins in calves with chronic bronchopneumonia. Twenty-eight calves with clinical symptoms of disease were included into the evaluation. Blood serum was analyzed for total protein concentrations (TP), total and relative values of serum protein fractions, albumin/globulin ratio (A/G) and the concentrations of selected acute phase proteins -haptoglobin (Hp), serum amyloid A (SAA), and fibrinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The authors did not fi nd blood lactate concentration to be useful in identifying early BRD, possibly because generalized body-tissue anaerobic metabolism did not have a chance to develop due to the low percentage of pulmonary involvement. Our results indicate higher lactate levels in calves with severe signs of respiratory disease, but these are frequently within the normal range [34][35][36]. Values over 1.5 mmol/l are considered risky regarding the prognosis and high proportion of animals, which die later on or must be culled from the herd.…”
Section: Discussionmentioning
confidence: 67%
“…The authors did not fi nd blood lactate concentration to be useful in identifying early BRD, possibly because generalized body-tissue anaerobic metabolism did not have a chance to develop due to the low percentage of pulmonary involvement. Our results indicate higher lactate levels in calves with severe signs of respiratory disease, but these are frequently within the normal range [34][35][36]. Values over 1.5 mmol/l are considered risky regarding the prognosis and high proportion of animals, which die later on or must be culled from the herd.…”
Section: Discussionmentioning
confidence: 67%
“…Serum protein electrophoresis can provide detailed information about pathological conditions related to protein profile. However, this method is rarely used in the diagnosis of bovine diseases (Apaydın and Dede, 2010;Dede et al 2014;Tóthová et al 2010;Tóthová et al 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of pneumonia is likely to increase survival, economic and animal welfare of heifers. There are many different agents in the etiology of respiratory diseases such as H. Somni, M. haemolytica, P. Multocidaetc. The diagnosis of calf pneumonia is based on clinical symptoms such as specific symptoms, depression and body temperature (Alacam and Sahal, 1997;Angen et al 2009;Batra et al 2003;Closs Jr. and Dechow, 2017;Snowder et al 2006;Tóthová et al 2013b;Turgut, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The flow diagram outlining the selection strategy to obtain 25 articles is summarized in Figure . Twenty‐three studies, , , were ultimately included. Two articles described studies already reported in different journals…”
Section: Resultsmentioning
confidence: 99%